Hormonal Receptor Expression in Endometrial Carcinoma: A Retrospective Immunohistochemical Study in a Nigerian Tertiary Hospital (2022)
Background Endometrial carcinoma is the commonest genital tract malignancy in most developed nations, but it lags behind cervical carcinoma and ovarian cancers in most developing nations, including Nigeria. Estrogen has been described as a promoter of endometrial carcinogenesis. Objectives The aim of this study was to demonstrate the frequency of estrogen receptor (ER) and progesterone receptor (PR) expressions in endometrial carcinoma and to correlate them with tumour grade. Materials and Methods Cases of endometrial carcinoma diagnosed in the Department of Pathology over a 10-year period were reviewed retrospectively. The paraffin-embedded blocks were retrieved, and immunohistochemistry for ER and PR was performed on them. Haematoxylin and eosin (H&E) slides were reviewed, and tumours were graded by three independent pathologists. Data were analysed using SPSS version 22. The level of significance was set at P ≤ 0.05. Results There were 44 cases of endometrial carcinoma. ER and PR were positive in 29.5% and 18.2% of cases, respectively. There was no significant association between ER (P = 0.361) and PR (P = 0.204) expressions and histological grade of the tumour. The most common histological grade was grade 3, with 70% of cases (36 cases), whereas 13 cases (26%) were grade 2 and only 2 cases (4%) were grade 1. Conclusion The positive expressions of ER and PR in endometrial carcinoma suggest that steroid receptor studies may be of potential benefit in the management of some patients with endometrial carcinoma. Future studies employing larger sample sizes are therefore recommended.